Changes in growth patterns due to nutritional adjustment in children of Northeast Brazil - Carlos A Bruno da Silva (19772745) (2014)
Objective Assess changes in height-weight chart development patterns in children enrolled in a nutritional intervention program. Materials and methods 188 children (83 girls and 105 boys) in the 6-months to 7-years age group were followed for 18 months. We performed an assessment of nutritional profile based on body mass index and cumulative variation of weight and height, anthropometric data of mid arm circumference, arm muscle area, and tricipital skin fold. Results Mean cumulative weight-height gain was 4.8 kg and 0.63 cm/month for the boys, and 5.2 kg and 0.66 cm/month for the girls (p < 0.05). Body mass index increased throughout follow-up. Arm muscle area and tricipital skin fold increased significantly during the follow-up period. Conclusion Nutritional intervention for 15 months was sufficient to cause changes in the development pattern of children between the ages of 6 months and 7 years, showing that the values obtained became normal over time. Based on the data obtained in this study, we conclude that children, regardless of their classification according to different nutritional assessment indices, respond satisfactory in terms of linear growth and associated height-weight development, after receiving calorie-protein nutritional adjustments. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2014.5